INTEGRITAS LAPORAN KEUANGAN: KEPEMILIKAN MANAJERIAL, KOMITE AUDIT, LEVERAGE DAN PROFITABILITAS - Abdul Karim Butar-Butar; Muh Hasan; Rika Mardiani (Jurnal Comparative: Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of Managerial Ownership, Audit Committee, Leverage (DER) and Profitability (ROA) on the Integrity of Financial Statements. This research is included in associative research (relationship). The population in this study were all property and real estate sub-sector companies listed on the Indonesia Stock Exchange for the period 2013 – 2017. The sample selection used a purposive sampling method. Based on predetermined criteria, a sample of 9 companies was obtained with a total population of 48 companies. The data analysis method used is panel data regression analysis. The results showed that managerial ownership, audit committee and leverage (DER) had no effect on the integrity of financial statements, while profitability (ROA) had an effect on the integrity of financial statements.